Protein-based halochromic electrospun nanosensor for monitoring trout fish freshness. (May 2020) - Aghaei, Zahra; Ghorani, Behrouz; Emadzadeh, Bahareh; Kadkhodaee, Rassoul; Tucker, Nick
Abstract: In the present study, a protein-based halochromic nanosensor was designed to assess the quality of rainbow trout fillets. Zein nanofibers containing alizarin as the indicator dye were electrospun. The sensors were characterised using SEM, FT-IR, DSC, XRD, dye leaching, response time experiments and colorimetric analysis. TVB-N, TVC and pH of fish fillets were also measured over 12 days of storage at 4°C. FT-IR results showed that the alizarin was incorporated in the zein matrix by intermolecular hydrogen bonding. DSC graphs of zein based samples showed that the temperature of dehydration, glass transition and protein unfolding in the halochromic nanofibers were lower than in powdered zein. The amorphous structure of the zein samples was confirmed by XRD analysis. No color changes were occurred in the first 4 days of storage, but later, a light purple color could be observed in the sensor by the naked eye. The color of sensor became magenta by the 10 th and 12 th day of cold storage indicating spoilage. This fabricated halochromic nanosensor can monitor fish freshness in real time through color changes. The colorimetric results correlated well with microbial and chemical changes in the fish. Graphical abstract: Image 1 Highlights: A zein electrospun nanosensor successfully monitored trout fish freshness. Trout fish spoilage induced alizarin color changes in zein nanofibers. Colorimetric results agreed with the microbial level changes in the fish. There is good correlation between TVBN levels and nanosensor color changes. The nanosensor provides high sensitivity real-time alerts for trout at 4°C.